Achieving Stabilization in Armenia - Horvath, Balazs (IMF Working Papers; Working Paper ;, 1998)
This paper examines the evolution, and impact on stabilization, of macroeconomic policies in Armenia during 1994-96. Fiscal and monetary policies have been effective in stabilizing the Armenian economy and facilitating significant growth, although they have not always worked in cohort. Seigniorage and the inflation tax declined dramatically as inflation fell, while dollarization was reversed but reached a plateau after mid-1995, affecting the demand for dram. The paper also presents quantitative indicators, which are suggestive of the trends discussed.